The assessment of impact of the construction and exploitation roads to abiotic and biotic factors of environment - Biernat, Krzysztof; Syta, Anna (Studia Ecologiae et Bioethicae, 2008)
The expansion of the road network in Poland and in world constitutes a considerable risk for the natural environment, this article is showing the most important effects of road investments, for example: pollutants of atmospheric air, the noise and vibrations, pollutants of waters and soils, the fragmentation of the space and the decline of the landscape. Everything is leading it for destroying the environment in which we live. Describing all threats to the environment with themselves a structure and an exploitation of roads are bringing which, is practically impossible, the man in the last years very much is interfering in the nature, instead of to protect it for next generations, therefore designers and entrepreneurs should concentrate on eliminating negative effects of construction and the more late exploitation of roads and for improvement in their technical state.